EFFECTS OF DIPLOMATIC RELATIONS ON ECONOMY OF CHINA - SERFRAZ, AYESHA (IJRDO - Journal of Business Management, 2016)
This study is a detailed discussion and analysis of china’s economy. The purpose of this study isto discuss China’s diplomatic relations with rest of the world and to determine that how it isbecoming the fastest growing economy. No econometric tests have been applied, it is a thoroughand comprehensive study of China’s political, economic and diplomatic policies. History of Chinahas been discussed under different political regimes with an in depth analysis of five year plans.Presently, China is the fastest growing economy and it is maintaining peace with rest of the worldto concentrate on development policies. Military built up of China has been analyzed and acomparison has been made between past and present military force. Special emphasis has beengiven towards Pakistan and China relations in accordance with Pakistan-China economicCorridor.